APAKAH GOODWILL BERPENGARUH TERHADAP RETURN SAHAM SYARIAH? - Mardiah, Kartawati; Riyani, Yani; Andriana, Susan (Jurusan Akuntansi Politeknik Negeri Pontianak, 2024)
This study aims to determine and analyze whether goodwill can affect the return of sharia stocks of entities listed on the Jakarta Islamic Index (JII) for the period 2020-2022. The research method is descriptive associative. The dependent variable in this study is Sharia Stock Return (Y) and the independent variable is Goodwill (X). Sampling using purposive sampling, obtained ten companies. Data were processed with simple linear regression using eViews. The study produced a significance value (Sig.) of 0.5897 which means it is greater than the probability of 0.05, meaning that Goodwill (X) has no effect on sharia stock returns at a significance level of 5%.